Oblikoslovje v panonski narečni skupini - Zorko, Terezija (Zinka) (Slavia Centralis, 2020)
Morphology of the Pannonian Dialectal Group The article compares word-formation and morphological patterns of the Pannonian dialect group with those found in Old Church Slavonic and in Standard Slovene. It includes a brief analysis of the dialectal phonological and stress system, discussing the dialectal endings and inflections (the three genders, especially the relatively unstable neuter; and the three numbers, as the dual is well preserved). Non-finite word classes used in the Pannonian dialects investigated, however, show relatively little variation.